Near-Death High-Frequency Hyper-Synchronization in the Rat Hippocampus - Zhang, Yujiao; Li, Zhenyi; Zhang, Jing; Zhao, Zongya; Zhang, Hongxing; Vreugdenhil, Martin; Lu, Chengbiao (Frontiers in Neuroscience, 2019)
The neural network oscillation appears to be closely correlated with brain state of consciousness. Under the condition of general anesthesia, the brain’s ability to integrate information was blocked, which means commonly losing of consciousness and impairing neuronal oscillation. However, what is the effect of anesthetics on neural activities at a larger dose? Chloral hydrate is a sedative-hypnotic drug which can enter in central nervous system, which has been used for anesthetic in animal. In the current study we found that application of overdose CH induced the highly synchronized neuronal network oscillations at gamma/beta frequency bands, but reduced theta oscillations and the alpha oscillations were unchanged. In addition, the gamma/beta oscillations showed high levels of interregional coherence in hippocampal CA1 and CA3 areas. These data demonstrate that chloral hydrate in the larger dose can induced hyper-synchronization in the rat hippocampus at near death state brain.